The External Morphology of Cucurbit Fly Dacus Ciliatus (Diptera: Tephritidae) in Iraq - Al-Asady, Hasan.S.; Al-Hasnawy, Hala.T.; Taweel, Aead.A Al. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study presents detailed description of external morphology of cucurbit fly Dacus ciliatus (Loew).  All available external morphological characters were used for all body regions and their appendages with regarding of chaetotaxy and male and female genitalia. Such characters were supported by drawings.